Inorganic structure repair material, repair method, and inorganic structure

A radical polymerized resin composition with specific additives addresses adhesion and durability issues in inorganic structures by maintaining strength and adhesion in wet conditions and resisting temperature-induced stress.

JP7625857B2Active Publication Date: 2025-02-04RESONAC CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020218040
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-25
Publication Date
2025-02-04
Estimated Expiration
2040-12-25

AI Technical Summary

Technical Problem

Conventional repair materials for inorganic structures fail to maintain adhesion in humid or water-immersed conditions and do not account for expansion and contraction due to temperature changes, leading to issues like cracking and peeling.

Method used

A radical polymerized resin composition containing metal soaps, metal complexes with β-diketone skeletons, thiols, a radical polymerization starter, and inorganic aggregates treated with a silane coupling agent, which form a mixture that maintains adhesion and strength even in wet conditions and withstands temperature-induced expansion and contraction.

Benefits of technology

The composition ensures excellent adhesion and resistance to cracking and peeling in various environmental conditions, providing a durable repair solution for inorganic structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625857000006
    Figure 0007625857000006
  • Figure 0007625857000007
    Figure 0007625857000007
  • Figure 0007625857000001
    Figure 0007625857000001
Patent Text Reader

Abstract

To provide a repair material for an inorganic structure, capable of exhibiting excellent adhesion and preventing the recurrence of degradation such as cracking and peeling-off of the repair material resulting from the expansion / shrinkage of the inorganic structure caused by a temperature change, even when a damaged part is in any of the following states, a dry state, a wet state, and a state of being immersed in water.SOLUTION: The repair material for an inorganic structure, includes a radically polymerizable resin composition containing the following (A) to (D), and the following inorganic aggregate (E), and satisfies the following (Physical property 1) and (Physical property 2). (A):at least one species of metal-containing compounds selected from metallic soap (A1) and a metal complex (A2) comprising a β-diketone skeleton, (B): at least one species of thiol compounds selected from a secondary thiol compound (B1) and a tertiary thiol compound (B2), (C): a radical polymerization initiator, (D): a radically polymerizable compound, (E):inorganic aggregate treated with a silane coupling agent, (Physical property 1): elongation at break of 1 to 15% after immersing the mixture of the radically polymerizable resin composition and the inorganic aggregate in water at a room temperature for 24 hours, and (Physical property 2): compression strength of 5 to 40 N / mm2 after immersing the mixture of the radically polymerizable resin composition and the inorganic aggregate in water at a room temperature for 24 hours.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an inorganic structure repair material that is applied to and hardened at a damaged area of ​​an inorganic structure to repair the damaged area, a repair method using the inorganic structure repair material, and an inorganic structure repaired using the inorganic structure repair material. Regarding. [Background technology]

[0002] In recent years, many inorganic structures, such as concrete, have been in use for more than 50 years. These inorganic structures have deteriorated due to simple weathering, neutralization, salt damage, as well as the effects of freezing and thawing through water and repeated drying and wetting, and many damaged areas exist.

[0003] As a method for repairing such damaged areas, a method has been disclosed in which the damaged area and its surroundings are removed, a specific epoxy resin is applied, a tack coat is then applied, and concrete or mortar is poured to repair the damaged area (Patent Document 1). However, although epoxy resin-based repair materials have excellent adhesion to dry concrete, they do not provide the desired adhesion in humid environments.

[0004] As a technique for solving these problems, a concrete repair material containing a radical polymerizable resin, a radical polymerizable monomer, and cyclodextrin has been disclosed (Patent Document 2). The concrete repair material of Patent Document 2 can achieve excellent adhesion not only to dry concrete but also to wet concrete. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] : JP 2013-256835 A [Patent Document 2] :Patent No. 5743043 Summary of the Invention [Problem to be solved by the invention]

[0006] However, none of the prior art techniques have examined the adhesiveness of repair materials used on damaged areas that are immersed in water. Furthermore, inorganic structures expand and contract with temperature changes, causing crack widths to change. However, none of the conventional techniques have considered the expansion and contraction caused by temperature changes, and so far the problem of re-deterioration, such as cracking and peeling of repair materials, caused by the expansion and contraction of inorganic structures with temperature changes has been overlooked.

[0007] The present invention has been made in consideration of the above technical background, and has an object to provide an inorganic structure repair material that can achieve excellent adhesion regardless of whether the damaged area is in a dry state, a wet state, or a state immersed in water, and that can prevent re-deterioration, such as cracking and peeling of the repair material, caused by the expansion and contraction of the inorganic structure accompanying temperature changes. [Means for solving the problem]

[0008] In order to achieve the above object, the present invention provides the following [1] to

[16] .

[0009] <Inorganic structure repair material> [1] An inorganic structure repair material comprising a radical polymerizable resin composition containing the following (A) to (D) and the following inorganic aggregate (E), and satisfying the following (Physical Property 1) and (Physical Property 2). (A) One or more metal-containing compounds selected from metal soaps (A1) and metal complexes having a β-diketone skeleton (A2). (B) One or more thiol compounds selected from secondary thiol compounds (B1) and tertiary thiol compounds (B2). (C) Radical polymerization initiator (D) Radical polymerizable compound (E) an inorganic aggregate treated with 0.001 to 15 parts by mass of a silane coupling agent relative to 100 parts by mass of a radical polymerizable compound (D); (Physical Property 1) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. The breaking elongation is 1 to 15%. (Property 2) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. After that, the compressive strength is 5 to 40 N / mm 2 [2] The inorganic structure repairing material according to [1], wherein the metal-containing compound (A) is contained in an amount of 0.001 to 5 parts by mass in terms of a metal component per 100 parts by mass of the radical polymerizable compound (D). [3] The inorganic structure repairing material according to [1] or [2], comprising 0.01 to 10 parts by mass of the thiol compound (B) relative to 100 parts by mass of the radical polymerizable compound (D). [4] The inorganic structure repairing material according to any one of [1] to [3], containing 100 to 800 parts by mass of the inorganic aggregate (E) per 100 parts by mass of the radical polymerizable compound (D). [5] The inorganic structure repair material according to any one of [1] to [4], wherein the silane coupling agent is represented by the general formula YCH2SiX3 [wherein X is a hydrolyzable substituent and Y is an organic functional group]. [6] The inorganic structure repair material according to [5], wherein X is at least one of a methoxy group and an ethoxy group. [7] The inorganic structure repair material according to [5], wherein Y is any one selected from the group consisting of a methacryloyloxy group, a vinyl group, an epoxy group, and an amino group.

[0010] <Repair method> [8] A method for repairing an inorganic structure, comprising applying a mixture containing a radical polymerizable resin composition containing the following (A) to (D) and the following inorganic aggregate (E), the mixture satisfying the following physical properties, to a damaged part of the inorganic structure and curing the mixture. (A) One or more metal-containing compounds selected from metal soaps (A1) and metal complexes having a β-diketone skeleton (A2). (B) One or more thiol compounds selected from secondary thiol compounds (B1) and tertiary thiol compounds (B2). (C) Radical polymerization initiator (D) Radical polymerizable compound (E) an inorganic aggregate treated with 0.001 to 15 parts by mass of a silane coupling agent relative to 100 parts by mass of a radical polymerizable compound (D); (Physical Property 1) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. The breaking elongation is 1 to 15%. (Property 2) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. After that, the compressive strength is 5 to 40 N / mm 2 [9] The method for repairing an inorganic structure according to [8], wherein the metal-containing compound (A) is contained in an amount of 0.001 to 5 parts by mass, calculated as a metal component, per 100 parts by mass of the radical polymerizable compound (D).

[10] The method for repairing an inorganic structure according to [8] or [9], wherein the thiol compound (B) is contained in an amount of 0.01 to 10 parts by mass per 100 parts by mass of the radical polymerizable compound (D).

[11] The method for repairing an inorganic structure according to any one of [8] to

[10] , wherein the mixture contains 100 to 800 parts by mass of the inorganic aggregate (E) per 100 parts by mass of the radical polymerizable compound (D).

[12] The method for repairing an inorganic structure according to any one of [8] to

[11] , wherein the silane coupling agent is represented by the general formula YCH2SiX3 [wherein X is a hydrolyzable substituent and Y is an organic functional group].

[13] The method for repairing an inorganic structure according to

[12] , wherein X is at least one of a methoxy group and an ethoxy group.

[14] The method for repairing an inorganic structure according to

[12] , wherein Y is any one selected from the group consisting of a methacryloyloxy group, a vinyl group, an epoxy group, and an amino group.

[15] The method for repairing an inorganic structure according to any one of [8] to

[14] , further comprising allowing the mixture to stand for 30 minutes or more, applying the mixture to the damaged area, and allowing the mixture to harden.

[0011] <Restored inorganic structure>

[16] An inorganic structure having a damaged area repaired using the inorganic structure repair material according to any one of [1] to [7]. Effect of the Invention

[0012] According to the present invention, it is possible to provide an inorganic structure repair material that can achieve excellent adhesion regardless of whether the damaged area is in a dry state, a wet state, or a state immersed in water, and that can avoid re-deterioration such as cracking and peeling of the repair material due to the expansion and contraction of the inorganic structure accompanying temperature changes. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is an explanatory diagram of a test specimen used in a crack follow-up test. [Diagram 2] FIG. 2 is an explanatory diagram of a crack follow-up test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The inorganic structure repairing material of the present invention and its manufacturing method, the repairing method using said inorganic structure repairing material, and the inorganic structure repaired using said inorganic structure repairing material will be described in detail below. In this specification, "normal temperature" means general room temperature within the range of 25±5°C. In the following description, the notation "A~B" indicating a numerical range represents a numerical range including the endpoints A and B. That is, it means "A or more and B or less" (when A < B), or "A or less and B or more" (when A > B). Also, parts by mass and mass% are synonymous with parts by weight and weight%, respectively.

[0015] [Inorganic structure repair material] The inorganic structure repair material of the present invention includes a radically polymerizable resin composition containing the following (A) to (D) and an inorganic aggregate of the following (E), and satisfies the following (Physical property 1) and (Physical property 2). (A) One or more metal-containing compounds selected from metal soaps (A1) and metal complexes (A2) having a β-diketone skeleton (B) One or more thiol compounds selected from secondary thiol compounds (B1) and tertiary thiol compounds (B2) (C) A radical polymerization initiator (D) A radically polymerizable compound (E) An inorganic aggregate treated with a silane coupling agent (Physical property 1) After mixing the radically polymerizable resin composition and the inorganic aggregate and immersing them in water at room temperature for 24 hours, the elongation at break is 1 to 15% (Physical property 2) After mixing the radically polymerizable resin composition and the inorganic aggregate and immersing them in water at room temperature for 24 hours, the compressive strength is 5 to 40 N / mm 2

[0016] Due to the elongation at break in (Physical property 1) being 1 to 15%, the followability to cracks becomes good. The compressive strength of (Physical property 2) is 5 to 40 N / mm 2 By being so, it is possible to ensure an appropriate strength as a repair material for inorganic structures.

[0017] [Radically polymerizable resin composition] [Metal-containing compound (A)] The radical polymerizable resin composition uses at least one metal-containing compound (A) selected from a metal soap (A1) and a metal complex (A2) having a β-diketone skeleton as a curing accelerator. The metal soap (A1) in the present invention refers to a salt of a long-chain fatty acid or an organic acid other than a long-chain fatty acid and a metal element other than potassium and sodium. The metal complex (A2) having a β-diketone skeleton in the present invention refers to a complex in which a compound having a structure in which one carbon atom is between two carbonyl groups is coordinated to a metal element.

[0018] The content of the metal-containing compound (A) in the radical polymerizable resin composition in terms of the metal component is preferably 0.001 to 5 parts by mass, more preferably 0.002 to 3 parts by mass, even more preferably 0.003 to 2.5 parts by mass, and even more preferably 0.004 to 2 parts by mass, relative to 100 parts by mass of the radical polymerizable compound (D) described below. When the content of the metal-containing compound (A) in terms of the metal component is within the above range, curing proceeds quickly even in water and in a humid atmosphere.

[0019] [Metal soap (A1)] The long-chain fatty acid in the metal soap (A1) is not particularly limited, but is preferably, for example, a fatty acid having 6 to 30 carbon atoms. Specifically, preferred are linear or cyclic saturated fatty acids such as octanoic acids such as heptanoic acid and 2-ethylhexanoic acid, nonanoic acid, decanoic acid, neodecanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosanoic acid, docosanoic acid, tetracosanoic acid, hexacosanoic acid, octacosanoic acid, triacontanoic acid, and naphthenic acid, and unsaturated fatty acids such as oleic acid, linoleic acid, and linolenic acid. Other examples include rosin acid, linseed oil fatty acid, soybean oil fatty acid, tall oil acid, and the like. The organic acid other than the long-chain fatty acid in the metal soap (A1) is not particularly limited, but is preferably a weak acid compound having a carboxy group, a hydroxy group, or an enol group, which is soluble in an organic solvent.

[0020] Examples of compounds having a carboxy group include carboxylic acids such as formic acid, acetic acid, and oxalic acid; hydroxy acids such as citric acid, bile acid, sugar acid, 12-hydroxystearic acid, hydroxycinnamic acid, and folic acid; amino acids such as alanine and arginine; and aromatic acids such as benzoic acid and phthalic acid. Examples of compounds having a hydroxy group or an enol group include ascorbic acid, alpha acid, imido acid, erythorbic acid, croconic acid, kojic acid, squaric acid, sulfinic acid, teichoic acid, dehydroacetic acid, delta acid, uric acid, hydroxamic acid, humic acid, fulvic acid, and phosphonic acid. Among these, long-chain fatty acids are preferred, linear or cyclic saturated fatty acids having 6 to 16 carbon atoms, or unsaturated fatty acids having 6 to 16 carbon atoms are more preferred, octanoic acid and naphthenic acid are even more preferred, and 2-ethylhexanoic acid and naphthenic acid are even more preferred.

[0021] Examples of the metal element constituting the metal soap (A1) include metal elements of Groups 1 and 2, such as lithium, magnesium, calcium, and barium; metal elements of Groups 3 to 12, such as titanium, zirconium, vanadium, manganese, iron, ruthenium, cobalt, rhodium, nickel, palladium, platinum, copper, silver, gold, and zinc; metal elements of Groups 13 and 14, such as aluminum, indium, tin, and lead; rare earth metal elements, such as neodymium and cerium; and bismuth. In one embodiment of the present invention, metal elements of Groups 2 to 12 are preferred, barium, vanadium, manganese, iron, cobalt, copper, titanium, and zinc are more preferred, manganese, iron, cobalt, copper, titanium, and zinc are even more preferred, and manganese, cobalt, and titanium are even more preferred. In another aspect of the present invention, metal elements of Groups 2 to 12 are preferred, zirconium, barium, vanadium, manganese, iron, cobalt, copper, titanium, bismuth, calcium, lead, tin and zinc are more preferred, zirconium, manganese, iron, cobalt, copper, titanium, bismuth, calcium, lead, tin and zinc are even more preferred, and zirconium, bismuth and calcium are even more preferred.

[0022] Specific examples of the metal soap (A1) in one embodiment of the present invention include manganese octylate, cobalt octylate, zinc octylate, vanadium octylate, cobalt naphthenate, copper naphthenate, and barium naphthenate, and more preferably manganese octylate, cobalt octylate, and cobalt naphthenate. In another embodiment of the present invention, zirconium octylate, manganese octylate, cobalt octylate, bismuth octylate, calcium octylate, zinc octylate, vanadium octylate, lead octylate, tin octylate, cobalt naphthenate, copper naphthenate, barium naphthenate, bismuth naphthenate, calcium naphthenate, lead naphthenate, and tin naphthenate are preferred, and zirconium octylate, manganese octylate, cobalt octylate, bismuth octylate, calcium octylate, lead octylate, tin octylate, bismuth naphthenate, calcium naphthenate, lead naphthenate, and tin naphthenate are more preferred.

[0023] [Metal complexes having a β-diketone skeleton (A2)] Examples of the metal complex (A2) having a β-diketone skeleton (hereinafter also referred to as "metal complex (A2)") include complexes formed between acetylacetone, ethyl acetoacetate, benzoylacetone, etc. and a metal. These metal complexes (A2) also exhibit the same functions as the metal soap (A1). Examples of the metal element constituting the metal complex (A2) include the same metal elements as those in the metal soap (A1).

[0024] In one embodiment of the present invention, specific examples of the metal complex (A2) include vanadium acetylacetonate, cobalt acetylacetonate, titanium acetylacetonate, titanium dibutoxybis(acetylacetonate), iron acetylacetonate, and cobalt ethyl acetoacetate, and among these, titanium acetylacetonate and titanium dibutoxybis(acetylacetonate) are more preferable. In another embodiment of the present invention, zirconium acetylacetonate, vanadium acetylacetonate, cobalt acetylacetonate, titanium acetylacetonate, titanium dibutoxybis(acetylacetonate), iron acetylacetonate, and cobalt ethyl acetoacetate are preferred, and among these, zirconium acetylacetonate, titanium acetylacetonate, and titanium dibutoxybis(acetylacetonate) are more preferred.

[0025] <Thiol Compound (B)> The radical polymerizable resin composition contains one or more thiol compounds (B) selected from a secondary thiol compound (B1) and a tertiary thiol compound (B2). In the present invention, the thiol compound (B) functions as a curing accelerator and is presumed to coordinate in the vicinity of the metal of the metal-containing compound (A) to prevent the metal from being deactivated by water. The thiol compound (B) used in the present invention is not particularly limited as long as it has one or more mercapto groups bonded to secondary or tertiary carbon atoms in the molecule (hereinafter, they may be referred to as "secondary mercapto groups" and "tertiary mercapto groups", respectively). However, from the viewpoint of rapidly proceeding with curing even in water and from the viewpoint of preventing the metal of the metal-containing compound (A) from being deactivated by water, a polyfunctional thiol, which is a compound having two or more secondary or tertiary mercapto groups in the molecule, is preferred, and among them, a bifunctional thiol, which is a compound having two secondary or tertiary mercapto groups in the molecule, is preferred. In addition, a secondary thiol compound (B1) is more preferred than a tertiary thiol compound (B2). As used herein, "polyfunctional thiol" refers to a thiol compound having two or more mercapto groups as functional groups, and "bifunctional thiol" refers to a thiol compound having two mercapto groups as functional groups.

[0026] The compound having two or more secondary or tertiary mercapto groups in the molecule is not particularly limited, but for example, a compound having at least one structure represented by the following formula (Q) and having two or more secondary or tertiary mercapto groups in the molecule including the mercapto group in the structure represented by the following formula (Q) is preferred.

[0027] [ka] (In formula (Q), R 1 is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aromatic group having 6 to 18 carbon atoms; R 2 is an alkyl group having 1 to 10 carbon atoms or an aromatic group having 6 to 18 carbon atoms, and * indicates that it is linked to an arbitrary organic group. a is an integer of 0 to 2.)

[0028] R in formula (Q) 1 is a hydrogen atom and has two or more secondary mercapto groups in the molecule. That is, the thiol compound (B) is preferably a secondary thiol compound (B1) in which the carbon atom to which the mercapto group in the formula (Q) is bonded is a secondary carbon atom. In addition, R in formula (Q) 1 and R 2 The alkyl group having 1 to 10 carbon atoms in the formula may be linear or branched. Specific examples include methyl, ethyl, various propyl, various butyl, various pentyl, various hexyl, various heptyl, and various octyl groups. Here, "various" refers to various isomers including n-, sec-, tert-, and iso-. Among these alkyl groups, methyl and ethyl are preferred. Examples of the aromatic group having 6 to 18 carbon atoms in R1 and R2 in formula (Q) include a phenyl group, a benzyl group, a naphthyl group, an anthryl group, a phenanthryl group, etc. These aromatic groups may be substituted with a halogen atom, an amino group, a nitro group, a cyano group, etc. In formula (Q), a is an integer of 0 to 2, and is preferably 1.

[0029] Furthermore, the thiol compound (B) preferably has at least one ester structure represented by the following formula (Q-1).

[0030] [ka] (In formula (Q-1), R 1 , R 2 , * and a represent R in the formula (Q). 1 , R 2 , * and a are synonymous.)

[0031] In formula (Q-1), a is preferably 1. When a is 1 and R1 is a hydrogen atom, that is, when the secondary thiol compound (B1) has an ester structure represented by (Q-1), it is considered that the carbonyl oxygen and the mercapto group are easily coordinated to the metal element such as cobalt of the metal-containing compound (A), as represented by the following formula (T), and the metal element of the metal-containing compound (A) is surrounded by the thiol compound. As a result, it is considered that the contact between the metal element and water can be suppressed. In the case of the tertiary thiol compound (B2), both R1 and R2 are substituents bulkier than hydrogen, and from the viewpoint of steric hindrance in the coordination of the mercapto group to the metal element, it is considered that the secondary thiol compound (B1) can exhibit a better curing acceleration performance. However, even in the tertiary thiol compound (B2), when the carbonyl oxygen and the mercapto group are stably coordinated to the metal element, it is considered that the contact between the metal element and water can be suppressed more than in the secondary thiol compound (B1).

[0032] [ka] (In formula (T), R 1 and R 2 is R in the formula (Q-1) 1 and R 2 and M represents a metal element derived from the metal-containing compound (A).

[0033] The thiol compound (B) having an ester structure represented by formula (Q-1) is a compound derived from a mercapto group-containing carboxylic acid represented by the following formula (S) and a polyhydric alcohol: is preferred.

[0034] [ka] (In formula (S), R 1 , R 2 and a is R in the formula (Q). 1 , R 2 and a.)

[0035] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, neopentyl glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,2-pentanediol, 1,3-pentanediol, 2,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, tricyclodecane dimethanol, (2,2-bis(2-hydroxyethoxyphenyl)propane), bisphenol A alkylene oxide adduct, bisphenol F alkylene oxide adduct, bisphenol S alkylene oxide adduct, 1,4-cyclohexyl ether, 1,2-diol, 1,3-diol, 1,4-cyclohexyl ether, 1,5- ...bisphenol A alkylene oxide adduct, bisphenol B alkylene oxide adduct, bisphenol C alkylene oxide adduct, bisphenol C alkylene oxide adduct, bisphenol C alkylene oxide adduct, bisphenol C alkylene oxide ad Dihydric alcohols such as xanediol, 1,4-cyclohexanedimethanol, 1,2-hexanediol, 1,3-hexanediol, 2,3-hexanediol, 1,4-hexanediol, 2,4-hexanediol, 3,4-hexanediol, 1,5-hexanediol, 2,5-hexanediol, 1,6-hexanediol, and 9,9-bis[4-(2-hydroxyethyl)phenyl]fluorene; trihydric or higher alcohols such as glycerin, diglycerin, trimethylolethane, trimethylolpropane, ditrimethylolpropane, tris(2-hydroxyethyl)isocyanurate, hexanetriol, sorbitol, pentaerythritol, dipentaerythritol, sucrose, and 2,2-bis(2,3-dihydroxypropyloxyphenyl)propane; and other polycarbonate diols and dimer acid polyester polyols. Among these, from the viewpoints of availability and improving curing properties in water, dihydric alcohols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, and 1,4-butanediol; trihydric or higher alcohols such as glycerin, trimethylolethane, trimethylolpropane, tris(2-hydroxyethyl)isocyanurate, pentaerythritol, dipentaerythritol, and 2,2-bis(2,3-dihydroxypropyloxyphenyl)propane; polycarbonate diols, and dimer acid polyester polyols are preferred, and from the viewpoints of the number of functional groups and vapor pressure, 1,4-butanediol, trimethylolethane, trimethylolpropane, tris(2-hydroxyethyl)isocyanurate, pentaerythritol, polycarbonate diols, and dimer acid polyester polyols are more preferred.

[0036] [Secondary thiol compound (B1)] When the thiol compound (B) having the structure represented by the formula (Q) is a secondary thiol compound (B1), specific examples thereof include 3-mercaptobutyric acid, di(1-mercaptoethyl) 3-mercaptophthalate, di(2-mercaptopropyl) phthalate, di(3-mercaptobutyl) phthalate, ethylene glycol bis(3-mercaptobutyrate), propyl Ethylene glycol bis(3-mercaptobutyrate), diethylene glycol bis(3-mercaptobutyrate), butanediol bis(3-mercaptobutyrate), octanediol bis(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptobutyrate), dipentaerythritol hexakis(3-mercaptobutyrate), ethylene glycol bis(2- mercaptopropionate), propylene glycol bis(2-mercaptopropionate), diethylene glycol bis(2-mercaptopropionate), butanediol bis(2-mercaptopropionate), octanediol bis(2-mercaptopropionate), trimethylolpropane tris(2-mercaptopropionate), pentaerythritol tetrakis(2-mercaptopropionate), dipentaerythritol hexakis(2-mercaptopropionate), ethylene glycol bis (4-mercaptovalerate), diethylene glycol bis(4-mercaptovalerate), butanediol bis(4-mercaptovalerate), octanediol bis(4-mercaptovalerate), trimethylolpropane tris(4-mercaptovalerate), pentaerythritol tetrakis(4-mercaptovalerate), dipentaerythritol hexakis(4-mercaptovalerate), ethylene glycol bis(3-mercaptovalerate), propylene glycol bis(3-mercaptovalerate) ), diethylene glycol bis(3-mercaptovalerate), butanediol bis(3-mercaptovalerate), octanediol bis(3-mercaptovalerate), trimethylolpropane tris(3-mercaptovalerate), pentaerythritol tetrakis(3-mercaptovalerate), dipentaerythritol hexakis(3-mercaptovalerate), hydrogenated bisphenol A bis(3-mercaptobutyrate), bisphenol A dihydroxyethyl ether-3-mercaptobutyrate, 4,Examples of the mercaptobutyrate include 4'-(9-fluorenylidene)bis(2-phenoxyethyl(3-mercaptobutyrate)), ethylene glycol bis(3-mercapto-3-phenylpropionate), propylene glycol bis(3-mercapto-3-phenylpropionate), diethylene glycol bis(3-mercapto-3-phenylpropionate), butanediol bis(3-mercapto-3-phenylpropionate), octanediol bis(3-mercapto-3-phenylpropionate), trimethylolpropane tris(3-mercapto-3-phenylpropionate), tris-2-(3-mercapto-3-phenylpropionate)ethyl isocyanurate, pentaerythritol tetrakis(3-mercapto-3-phenylpropionate), and dipentaerythritol hexakis(3-mercapto-3-phenylpropionate). ,

[0037] In addition, when the secondary thiol compound (B1) is a compound having an ester structure represented by the formula (Q-1), this compound is preferably derived from the polyhydric alcohol and a carboxylic acid containing a secondary mercapto group represented by the formula (S). Examples of the mercapto group-containing carboxylic acid represented by the formula (S) include 2-mercaptopropionic acid, 3-mercaptobutyric acid, and 3-mercapto-3-phenylpropionic acid.

[0038] Of the secondary thiol compounds (B1), commercially available compounds having two or more secondary mercapto groups in the molecule include 1,4-bis(3-mercaptobutyryloxy)butane (manufactured by Showa Denko K.K., KarenzMT (registered trademark) BD1), pentaerythritol tetrakis(3-mercaptobutyrate) (manufactured by Showa Denko K.K., KarenzMT (registered trademark) PE1), 1,3,5-tris[2-(3-mercaptobutyryloxyethyl)]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (manufactured by Showa Denko K.K., KarenzMT (registered trademark) NR1), trimethylolethane tris(3-mercaptobutyrate) (manufactured by Showa Denko K.K., TEMB), and trimethylolpropane tris(3-mercaptobutyrate) (manufactured by Showa Denko K.K., TPMB), and it is preferable to use one or more of these.

[0039] [Tertiary thiol compounds (B2)] When the thiol compound (B) having a structure represented by the formula (Q) is a tertiary thiol compound (B2), specific examples thereof include di(2-mercaptoisobutyl)phthalate, ethylene glycol bis(2-mercaptoisobutyrate), propylene glycol bis(2-mercaptoisobutyrate), diethylene glycol bis(2-mercaptoisobutyrate), butanediol bis(2-mercaptoisobutyrate), octanediol bis(2-mercaptoisobutyrate), trimethylolethane tris(2-mercaptoisobutyrate), trimethylolpropane tris(2-mercaptoisobutyrate), pentaerythritol tetrakis(2-mercaptoisobutyrate), dipentaerythritol hexakis(2-mercaptoisobutyrate), and the like. butylate), di(3-mercapto-3-methylbutyl)phthalate, ethylene glycol bis(3-mercapto-3-methylbutyrate), propylene glycol bis(3-mercapto-3-methylbutyrate), diethylene glycol bis(3-mercapto-3-methylbutyrate), butanediol bis(3-mercapto-3-methylbutyrate), octanediol bis(3-mercapto-3-methylbutyrate), trimethylolethane tris(3-mercapto-3-methylbutyrate), trimethylolpropane tris(3-mercapto-3-methylbutyrate), pentaerythritol tetrakis(3-mercapto-3-methylbutyrate), dipentaerythritol hexakis(3-mercapto-3-methylbutyrate), and the like.

[0040] In addition, when the tertiary thiol compound (B2) is a compound having an ester structure represented by the formula (Q-1), this compound is preferably derived from the polyhydric alcohol and a carboxylic acid containing a tertiary mercapto group represented by the formula (S). Examples of the mercapto group-containing carboxylic acid represented by the formula (S) include 2-mercaptoisobutyric acid and 3-mercapto-3-methylbutyric acid.

[0041] [Esterification reaction of mercapto group-containing carboxylic acid represented by formula (S) with polyhydric alcohol] The esterification reaction between the mercapto group-containing carboxylic acid represented by the formula (S) and the polyhydric alcohol is not particularly limited, and the polyhydric alcohol can be produced by a general esterification reaction. The reaction temperature of the esterification reaction is preferably 60 to 160° C., more preferably 60 to 135° C., from the viewpoint of rapidly progressing the reaction and suppressing the production of by-products. Note that, from the viewpoint of suppressing the production of by-products, it is preferable to carry out the reaction while removing water produced by the esterification reaction.

[0042] In the esterification reaction, a solvent may or may not be used, but from the viewpoint of improving the reaction rate, it is preferable to use a solvent that forms an azeotropic mixture with water. Examples of the solvent that forms an azeotropic mixture with water include toluene, xylene, cyclohexane, and ethylbenzene, and from the viewpoint of the balance between the production cost and the obtained effect, toluene is preferable. The amount of the solvent that forms an azeotropic mixture with water is preferably 10 to 90 mass % in the reaction system. The mercapto group-containing carboxylic acid represented by formula (S) and the polyhydric alcohol are preferably used such that the carboxyl group of the mercapto group-containing carboxylic acid represented by formula (S) is 1.0 to 4.0 equivalents per equivalent of the hydroxyl group of the polyhydric alcohol. When the carboxyl group equivalent of the mercapto group-containing carboxylic acid represented by formula (S) is 1.0 equivalent or more, the amount of unreacted hydroxyl groups can be reduced, and the number of mercapto groups in one molecule is two or more, improving the curability, and when the carboxyl group is 4.0 equivalents or less, the production cost can be reduced.

[0043] The catalyst used in the esterification reaction is preferably a non-volatile acid catalyst, and specific examples thereof include inorganic acids such as sulfuric acid, perchloric acid, phosphoric acid, etc., and organic acids such as p-toluenesulfonic acid, methanesulfonic acid, levulinic acid, etc. Among these, sulfuric acid, p-toluenesulfonic acid, methanesulfonic acid, etc. are preferred from the viewpoint of reaction rate. The non-volatile acid catalyst refers to an acid catalyst having a vapor pressure of 1 kPa or less at 25°C. The amount of the catalyst used is preferably 0.01 to 1.0 mol per 1 mol of the hydroxyl group of the polyhydric alcohol. When the amount of the catalyst used is 0.01 mol or more, the reaction rate becomes sufficiently fast, and when the amount is 1.0 mol or less, the amount of the basic substance used in neutralization performed after the reaction can be reduced.

[0044] The reaction pressure of the esterification reaction is not particularly limited, but is preferably 100 to 760 mmHg from the viewpoint of improving the reaction rate, and more preferably 300 to 550 mmHg from the viewpoint of dehydration efficiency. When the reaction pressure is within the above range, the temperature in the reaction system becomes high, and the reaction easily proceeds.

[0045] The end of the reaction can be judged by the amount of water extracted from the reaction system, and it is preferable to carry out the reaction until the amount of water reaches the theoretical value of the amount of water removed by the esterification reaction, but if the reaction takes a long time, the reaction can be terminated when 80% by mass or more of the theoretical value of water has been removed. If the amount of water is 80% by mass or more of the theoretical value of the amount of water removed by the esterification reaction, there is little unreacted polyhydric alcohol, and therefore the curability of the radical polymerizable resin composition of the present invention is improved.

[0046] After the reaction is completed, it is preferable to neutralize the acid catalyst. Although there is no particular limitation on the basic substance for neutralization, sodium bicarbonate and caustic soda are preferable from the viewpoint of reducing costs, and sodium bicarbonate is more preferable from the viewpoint of ease of adjusting the pH. After the reaction is completed, extraction may be performed in order to purify the target product. As the extraction solvent when extraction is performed, toluene, ethyl acetate, isopropyl acetate, and butyl acetate are preferred in terms of volatility, and toluene and ethyl acetate are more preferred in terms of the cost of the extraction solvent. In addition, a hydrophobic solvent may be added to the extraction solvent in order to improve the separation speed during extraction, and hexane and heptane are more preferred in terms of the separation speed and the cost of the hydrophobic solvent.

[0047] In the solvent distillation step, the solvent is distilled off under heating and reduced pressure conditions, and the distillation temperature is preferably 80 to 150° C. regardless of the degree of reduced pressure. If the temperature is within the above range, the solvent can be completely distilled off and polymerization between the synthesized thiol compounds can be prevented.

[0048] The molecular weight of the thiol compound (B) in the present invention is not particularly limited, but is preferably low, specifically, preferably 5,000 or less, more preferably 2,500 or less, even more preferably 1,500 or less, and even more preferably 750 or less. Also, it is preferably 100 or more, more preferably 150 or more, and even more preferably 200 or more. In the present invention, the molecular weight refers to the number average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC method).

[0049] The total amount of the thiol compound (B) in the radical polymerizable resin composition is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 7 parts by mass, even more preferably 0.1 to 5 parts by mass, and even more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the radical polymerizable compound (D) described below. When the amount of the thiol compound (B) is 0.01 parts by mass or more, the curing function can be sufficiently obtained, and when it is 10 parts by mass or less, the curing proceeds quickly.

[0050] The total molar ratio [(B) / (A)] of the thiol compound (B) to the metal component of the metal-containing compound (A) is preferably 0.1 to 15, more preferably 0.3 to 10, even more preferably 0.6 to 8, and even more preferably 0.8 to 5. When the molar ratio [(B) / (A)] is 0.1 or more, the thiol compound (B) can be sufficiently coordinated in the vicinity of the metal of the metal-containing compound (A), and when the molar ratio is 15 or less, the balance between the production cost and the effect is improved.

[0051] The thiol compound (B) may be used alone or in combination of two or more. When a secondary thiol compound (B1) and a tertiary thiol compound (B2) are used in combination, the molar ratio [(B1) / (B2)] of the two is preferably 0.001 to 1000, more preferably 1 to 10. When the molar ratio [(B1) / (B2)] is within the above range, the metal soap (A) and the thiol compound (B) are stable in the state of the above formula (T) in the radical polymerizable resin composition, and a disulfide compound caused by the bond between the thiol compounds (B) is not generated as a by-product. From the viewpoint of storing the radical polymerizable resin composition with the metal soap (A) and the thiol compound (B) in a stable state, it is preferable to use the secondary thiol compound (B1) or the tertiary thiol compound (B2) alone.

[0052] <Radical polymerization initiator (C)> The radical polymerizable resin composition preferably contains a radical polymerization initiator (C) as a curing agent. Examples of the radical polymerization initiator (C) include a thermal radical polymerization initiator (C-1) and a photoradical polymerization initiator (C-2). Examples of the thermal radical polymerization initiator (C-1) include organic peroxides such as diacyl peroxides such as benzoyl peroxide, peroxy esters such as tert-butyl peroxybenzoate, hydroperoxides such as cumene hydroperoxide, dialkyl peroxides such as dicumyl peroxide, ketone peroxides such as methyl ethyl ketone peroxide and acetylacetone peroxide, peroxy ketals, alkyl peresters, and percarbonates. Examples of the photoradical polymerization initiator (C-2) include benzoin ether-based initiators such as benzoin alkyl ether; benzophenone-based initiators such as benzophenone, benzil, and methyl orthobenzoyl benzoate; acetophenone-based initiators such as benzil dimethyl ketal, 2,2-diethoxyacetophenone, 2-hydroxy-2-methylpropiophenone, 4-isopropyl-2-hydroxy-2-methylpropiophenone, and 1,1-dichloroacetophenone; and thioxanthone-based initiators such as 2-chlorothioxanthone, 2-methylthioxanthone, and 2-isopropylthioxanthone. Photoradical polymerization initiators (C-2) that are sensitive to light from ultraviolet light to visible light include acetophenones, benzil ketals, and (bis)acylphosphine oxides. Examples of known initiators that can be used for this purpose include, specifically, Irgacure 1700 (trade name, manufactured by Ciba Specialty Chemicals Co., Ltd.), which is a mixture of 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Darocur 1173, manufactured by Ciba Specialty Chemicals Co., Ltd.) and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide (manufactured by Ciba Specialty Chemicals Co., Ltd.) in a ratio of 75% / 25%; Irgacure 184 (trade name, manufactured by Ciba Specialty Chemicals Co., Ltd.) and 1-hydroxycyclohexyl phenyl ketone (trade name: Irgacure 184, manufactured by Ciba Specialty Chemicals Co., Ltd.) and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide (manufactured by Ciba Specialty Chemicals Co., Ltd.), which is a mixture of ...), and bis(2, (trade name: Irgacure 1800, manufactured by Chiba Specialty Chemicals Co., Ltd.) mixed with 2,4,4-trimethylpentyl phosphine oxide (manufactured by Chiba Specialty Chemicals Co., Ltd.) in a ratio of 75% / 25% (trade name: Irgacure 1800, manufactured by Chiba Specialty Chemicals Co., Ltd.), and mixed with 50% / 50% (trade name: Irgacure 1850, manufactured by Chiba Specialty Chemicals Co., Ltd.); bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name: Irgacure 819, manufactured by Chiba Specialty Chemicals Co., Ltd.); 2,4,6-trimethylbenzoyldiphenylphosphine oxide (trade name: Lucirin TPO, manufactured by BASF Ltd.); Darocur 4265, which is a 50% / 50% mixture of 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Darocur 1173, manufactured by Chiba Specialty Chemicals Co., Ltd.) and 2,4,6-trimethylbenzoyldiphenylphosphine oxide (trade name: Lucirin TPO, manufactured by BASF Ltd.). Examples of the photoradical polymerization initiator (C-2) having photosensitivity in the visible light region include camphorquinone, benzyltrimethylbenzoyldiphenylphosphinoxide, methylthioxanthone, and dicyclopentadiethyltitanium-di(pentafluorophenyl). These radical polymerization initiators (C) may be used alone or in combination of two or more. In order to support the main reaction between heat curing and photocuring, the other reaction may be introduced, and the heat radical polymerization initiator (C-1) and the photoradical polymerization initiator (C-2) may be used in combination as necessary. In addition, depending on the molding conditions, they can also be used in composite forms such as organic peroxide / dye system, diphenyl iodide salt / dye system, imidazole / keto compound, hexaarylbiimidazole compound / hydrogen donor compound, mercaptobenzothiazole / thiopyrylium salt, metal arene / cyanine dye, and hexaarylbiimidazole / radical generator.

[0053] The amount of the radical polymerization initiator (C) is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and further preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the radically polymerizable compound (D).

[0054] <Radical polymerizable compound (D)> The radical polymerizable resin composition uses a radical polymerizable compound (D) as a base material. In the present invention, the radical polymerizable compound (D) refers to a compound that has an ethylenically unsaturated group in the molecule and undergoes a polymerization reaction by a radical. Examples of the radically polymerizable compound (D) include vinyl ester resins (epoxy (meth)acrylate resins), unsaturated polyester resins, polyester (meth)acrylate resins, urethane (meth)acrylate resins, (meth)acrylate resins, radically polymerizable unsaturated monomers, and mixtures of the above resins with radically polymerizable unsaturated monomers, among which at least one selected from vinyl ester resins, unsaturated polyester resins, and mixtures of these with radically polymerizable unsaturated monomers are preferred. In this specification, "(meth)acrylate" means "acrylate or methacrylate".

[0055] [Vinyl ester resin] As the vinyl ester resin, a resin obtained by reacting an epoxy resin with an unsaturated monobasic acid can be used.

[0056] Epoxy resins include bisphenol A diglycidyl ether and its high molecular weight homologues, novolac-type glycidyl ethers, and the like. Specifically, bisphenol type epoxy resins (for example, those obtained by reacting bisphenols such as bisphenol A, bisphenol F, bisphenol S, and tetrabromobisphenol A with epichlorohydrin and / or methylepichlorohydrin, or those obtained by reacting a glycidyl ether of bisphenol A with a condensate of the bisphenols with epichlorohydrin and / or methylepichlorohydrin, etc.), biphenyl type epoxy resins (for example, those obtained by reacting biphenol with epichlorohydrin and / or methylepichlorohydrin), naphthalene type epoxy resins (for example, those obtained by reacting dihydroxynaphthalene with epichlorohydrin and / or methylepichlorohydrin), aralkyldiphenol type epoxy resins (for example, those obtained by reacting aralkylphenol with epichlorohydrin and / or methylepichlorohydrin, etc.), Examples of epoxy resins include epoxy resins having an oxazolidone ring obtained by reacting the epoxy resin with a diisocyanate (specific examples include Araldite (registered trademark) AER4152 manufactured by Asahi Kasei Epoxy Co., Ltd.), novolak type epoxy resins (e.g., those obtained by reacting phenol novolak or cresol novolak with epichlorohydrin and / or methyl epichlorohydrin, etc.), trisphenolmethane type epoxy resins (e.g., those obtained by reacting trisphenolmethane, triscretholmethane with epichlorohydrin and / or methyl epichlorohydrin, etc.), and the like.

[0057] The unsaturated monobasic acid may be a known one, such as (meth)acrylic acid, crotonic acid, or cinnamic acid. A reaction product of a compound having one hydroxyl group and one or more (meth)acryloyl groups with a polybasic acid anhydride may also be used. In this specification, "(meth)acrylic acid" means one or both of "acrylic acid and methacrylic acid", and "(meth)acryloyl group" means one or both of "acryloyl group and methacryloyl group". The polybasic acid is used to increase the molecular weight of the epoxy resin, and known polybasic acids can be used. Examples include succinic acid, glutaric acid, adipic acid, sebacic acid, phthalic acid, fumaric acid, maleic acid, itaconic acid, tetrahydrophthalic acid, hexahydrophthalic acid, dimer acid, ethylene glycol 2 moles maleic anhydride adduct, polyethylene glycol 2 moles maleic anhydride adduct, propylene glycol 2 moles maleic anhydride adduct, polypropylene glycol 2 moles maleic anhydride adduct, dodecanedioic acid, tridecanedioic acid, octadecanedioic acid, 1,16-(6-ethylhexadecane)dicarboxylic acid, 1,12-(6-ethyldodecane)dicarboxylic acid, carboxyl group-terminated butadiene-acrylonitrile copolymer (trade name: Hycar CTBN), etc.

[0058] [Unsaturated polyester resin] As the unsaturated polyester resin, a resin obtained by subjecting a dibasic acid component containing an unsaturated dibasic acid and, if necessary, a saturated dibasic acid, to an esterification reaction with a polyhydric alcohol component can be used. Examples of the unsaturated dibasic acid include maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, etc., which may be used alone or in combination of two or more kinds. Examples of the saturated dibasic acid include aliphatic dibasic acids such as adipic acid, suberic acid, azelaic acid, sebacic acid, and isosebacic acid; aromatic dibasic acids such as phthalic acid, phthalic anhydride, halogenated phthalic anhydride, isophthalic acid, terephthalic acid, tetrachlorophthalic acid, tetrachlorophthalic anhydride, dimer acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid anhydride, 4,4'-biphenyldicarboxylic acid, and dialkyl esters thereof; and halogenated saturated dibasic acids. These may be used alone or in combination of two or more.

[0059] The polyhydric alcohol is not particularly limited, and examples thereof include ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-methyl-1,3-propanediol, 2-methyl-1,4-butanediol, 2,2-dimethyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, 3-methyl-1,5-pentanediol, diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, 1,2-cyclohexanediol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,6 ... Examples of the dihydric alcohols include hexane glycol, 1,3-cyclohexane glycol, 1,4-cyclohexane glycol, 1,4-cyclohexanedimethanol, paraxylene glycol, bicyclohexyl-4,4'-diol, 2,6-decalin glycol, and 2,7-decalin glycol; dihydric alcohols such as adducts of dihydric phenols such as hydrogenated bisphenol A, cyclohexanedimethanol, bisphenol A, bisphenol F, bisphenol S, and tetrabromobisphenol A with alkylene oxides such as propylene oxide or ethylene oxide; and trihydric or higher alcohols such as 1,2,3,4-tetrahydroxybutane, glycerin, trimethylolpropane, and pentaerythritol.

[0060] The unsaturated polyester may be modified with a dicyclopentadiene compound within the scope of the present invention. The modification method with a dicyclopentadiene compound may include a known method in which, for example, an addition product of dicyclopentadiene and maleic acid (cydecanol monomaleate) is obtained, and then the product is used as a monobasic acid to introduce a dicyclopentadiene skeleton. An oxidative polymerization group can be introduced into the vinyl ester resin or unsaturated polyester resin used in the present invention. There is no particular limitation on the method of introduction, but examples thereof include the addition of an oxidative polymerization group-containing polymer, condensation of a compound having a hydroxyl group and an allyl ether group, and addition of a reaction product of a compound having a hydroxyl group and an allyl ether group and an acid anhydride to allyl glycidyl ether or 2,6-diglycidyl phenyl allyl ether.

[0061] [Polyester (meth)acrylate resin, urethane (meth)acrylate resin, and (meth)acrylate resin] The polyester (meth)acrylate resin in the present invention may be, for example, a polyester obtained by reacting a polyvalent carboxylic acid with a polyhydric alcohol, specifically, a resin obtained by reacting (meth)acrylic acid with hydroxyl groups at both ends of polyethylene terephthalate or the like. Furthermore, as the urethane (meth)acrylate resin, for example, a resin obtained by reacting (meth)acrylic acid with hydroxyl groups or isocyanato groups at both ends of polyurethane obtained by reacting isocyanate with polyhydric alcohol can be used. Examples of the (meth)acrylate resin that can be used include poly(meth)acrylic resins having one or more substituents selected from a hydroxyl group, an isocyanato group, a carboxyl group, and an epoxy group, and resins obtained by reacting a (meth)acrylic acid ester having a hydroxyl group with a substituent of a polymer of a monomer having the above substituent and a (meth)acrylate.

[0062] [Radically polymerizable unsaturated monomer] In the present invention, a radically polymerizable unsaturated monomer can be used as the radically polymerizable compound (D). The radical polymerizable unsaturated monomer may be used alone, but it is preferable to use the radical polymerizable unsaturated monomer as a mixture with at least one of the vinyl ester resin and the unsaturated polyester resin. There are no particular limitations on the radically polymerizable unsaturated monomer, but those having a vinyl group or a (meth)acryloyl group are preferred. Specific examples of monomers having a vinyl group include styrene, p-chlorostyrene, vinyltoluene, α-methylstyrene, dichlorostyrene, divinylbenzene, tert-butylstyrene, vinyl acetate, diallyl phthalate, and triallyl isocyanurate.

[0063] Specific examples of monomers having a (meth)acryloyl group include (meth)acrylic acid esters.Specifically, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, stearyl (meth)acrylate, tridecyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, phenoxyethyl methacrylate, 2-hydroxyethyl methacrylate, ethylene glycol monomethyl ether (meth)acrylate, ethylene glycol monoethyl ether (meth)acrylate, ethylene glycol monobutyl ether (meth)acrylate, ethylene glycol monohexyl ether (meth)acrylate, ethylene glycol mono 2-ethylhexyl ether (meth)acrylate, diethylene glycol monomethyl ether (meth)acrylate, diethylene glycol monoethyl ether (meth)acrylate, diethylene glycol monobutyl ether (meth)acrylate, diethylene glycol monoethyl ether (meth)acrylate, diethylene glycol monohexyl ether (meth)acrylate, diethylene glycol mono 2-ethylhexyl ether (meth)acrylate, neopentyl glycol di(meth)acrylate, dimethacrylate of PTMG, 1,3-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 2-hydroxy-1,3-dimethacryloxypropane, 2,2-bis[4-(methacryloylethoxy)phenyl]propane, 2,2-bis[4-(methacryloxy Examples of the acrylates include 2,2-bis[4-(methacryloxy-polyethoxy)phenyl]propane, 2,2-bis[4-(methacryloxy-polyethoxy)phenyl]propane, tetraethylene glycol diacrylate, bisphenol A EO-modified (n=2) diacrylate, isocyanuric acid EO-modified (n=3) diacrylate, pentaerythritol diacrylate monostearate, dicyclopentenyl acrylate, dicyclopentenyloxyethyl acrylate, tricyclodecanyl (meth)acrylate, and tris(2-hydroxyethyl)isocyanuracrylate.

[0064] Further, examples of polyfunctional (meth)acrylic acid esters include alkanediol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,2-propylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate; diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and triethylene glycol (meth)acrylate. polyoxyalkylene glycol di(meth)acrylates such as tetraethylene glycol di(meth)acrylate and polyethylene glycol (meth)acrylate; trimethylolpropane di(meth)acrylate, glycerin di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Furthermore, the following compounds can also be used as the radical polymerizable unsaturated monomer.Specific examples include divinylbenzene, diallyl phthalate, triallyl phthalate, triallyl cyanurate, triallyl isocyanurate, allyl (meth)acrylate, diallyl fumarate, allyl methacrylate, vinylbenzyl butyl ether, vinylbenzyl hexyl ether, vinylbenzyl octyl ether, vinylbenzyl (2-ethylhexyl) ether, vinylbenzyl (β-methoxymethyl) ether, vinylbenzyl (n-butoxypropyl) ether, vinylbenzyl cyclohexyl ether, vinylbenzyl (β-phenoxyethyl) ether, vinylbenzyl dicyclopentenyl ether, vinylbenzyl dicyclopentenyloxyethyl ether, vinylbenzyl dicyclopentenyl methyl ether, and divinylbenzyl ether. In addition to the above, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate and the like can also be used. These may be used alone or in combination of two or more.

[0065] The radical polymerizable unsaturated monomer can be used to reduce the viscosity of the radical polymerizable resin composition of the present invention and improve hardness, strength, chemical resistance, water resistance, etc., but if the content is too high, it may lead to deterioration of the cured product or environmental pollution. Therefore, the content of the radical polymerizable unsaturated monomer in the radical polymerizable compound (D) is preferably 90 mass% or less. Furthermore, when the radical polymerizable compound (D) contains styrene as a radical polymerizable unsaturated monomer, the content is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 20% by mass or less, and even more preferably 5% by mass or less. If the content of styrene in the radical polymerizable compound (D) exceeds 60% by mass, the styrene may dissolve in water, and the cured product may become brittle, which is not preferable.

[0066] The radically polymerizable compound (D) may contain residual catalysts and polymerization inhibitors used in synthesizing the vinyl ester resin, the unsaturated polyester resin, the polyester (meth)acrylate resin, the urethane (meth)acrylate resin, and the (meth)acrylate resin. Examples of the catalyst include triethylamine, pyridine derivatives, imidazole derivatives, compounds containing tertiary nitrogen such as imidazole derivatives; amine salts such as tetramethylammonium chloride and triethylamine; and phosphorus compounds such as trimethylphosphine and triphenylphosphine. Examples of the polymerization inhibitor include hydroquinone, methylhydroquinone, and phenothiazine. When the catalyst or polymerization inhibitor remains in the radically polymerizable compound (D), the amount thereof is preferably 0.001 to 2 parts by mass, respectively, per 100 parts by mass of the vinyl ester resin and the unsaturated polyester resin in total.

[0067] The content of the radical polymerizable compound (D) in the radical polymerizable resin composition of the present invention is preferably 10 to 99.9 mass%, more preferably 80 to 99.9 mass%, even more preferably 85 to 99.5 mass%, and still more preferably 90 to 99.5 mass%. When the content of the radical polymerizable compound (D) in the radical polymerizable resin composition is within the above range, the hardness of the cured product is further improved.

[0068] [Inorganic aggregate] <Inorganic aggregate treated with silane coupling agent (E)> By contacting the surface of inorganic aggregate with a low-concentration aqueous solution or organic solvent solution of a silane coupling agent, the hydroxyl groups present on the surface of the inorganic aggregate react with the silanol groups generated by hydrolysis of the silane coupling agent, or the oligomers generated by condensation of the silanol groups are adsorbed on the surface of the inorganic aggregate, and strong chemical bonds are formed by drying treatment. In this way, functional groups capable of forming chemical bonds that enable strong adhesion between the radical polymerizable compound and the inorganic aggregate during polymerization are introduced. The inorganic aggregate is preferably a premixed aggregate in which cement is mixed in advance with silica sand, insulator powder, etc. By including silica sand, insulator powder, etc., the dimensional stability of the repair material is improved, and the coating thickness during construction can be stabilized.

[0069] The content of the inorganic aggregate (E) in the inorganic structure repairing material is preferably 100 to 800 parts by mass, more preferably 200 to 500 parts by mass, per 100 parts by mass of the radical polymerizable compound (D).

[0070] When treating the inorganic aggregate (E) with a silane coupling agent, the silane coupling agent may be directly sprayed, but a method of spraying an aqueous solution or an organic solvent solution of the silane coupling agent and drying is preferable. The inorganic aggregate may be immersed in an aqueous solution or an organic solvent solution of the silane coupling agent and then dried. The concentration of the silane coupling agent in the aqueous solution or organic solvent is 0.01 to 10% by mass, preferably 0.1 to 2% by mass. The amount of the silane coupling agent added is 0.001 to 15 parts by mass, preferably 0.01 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the radical polymerizable compound (D). By making the amount of the silane coupling agent added 0.001 parts by mass or more, the necessary physical properties required in the present invention can be realized. By making the amount of the silane coupling agent added 15 parts by mass or less, adverse effects on other physical properties can be avoided.

[0071] [Silane coupling agent] The silane coupling agent may be a known one used for surface treatment of glass fibers or the like. The silane coupling agents used include vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-amino Propylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminopropyltrimethoxysilane hydrochloride, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-isocyanatepropyltriethoxysilane, dithioltriazinepropyltriethoxysilane, and the like. The silane coupling agent is preferably represented by the general formula YCH2SiX3, where X is a hydrolyzable substituent and Y is an organic functional group. In the formula, X is preferably at least one of a methoxy group and an ethoxy group, and Y is preferably any one selected from the group consisting of a methacryloyloxy group, a vinyl group, an epoxy group, and an amino group.

[0072] [Repair method] The repair method according to the present invention comprises applying a mixture containing a radical polymerizable resin composition containing the following (A) to (D) and the following inorganic aggregate (E) and satisfying the following physical properties to a damaged part of an inorganic structure and curing the mixture. The mixture is preferably left to stand for 30 minutes or more, and then applied to the damaged part and cured. (A) One or more metal-containing compounds selected from metal soaps (A1) and metal complexes having a β-diketone skeleton (A2). (B) One or more thiol compounds selected from secondary thiol compounds (B1) and tertiary thiol compounds (B2). (C) Radical polymerization initiator (D) Radical polymerizable compound (E) an inorganic aggregate treated with 0.001 to 15 parts by mass of a silane coupling agent relative to 100 parts by mass of a radical polymerizable compound (D); (Physical Property 1) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. The breaking elongation is 1 to 15%. (Property 2) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. After that, the compressive strength is 5 to 40 N / mm 2

[0073] The metal-containing compound (A) is preferably contained in an amount of 0.001 to 5 parts by mass, calculated as the metal component, relative to 100 parts by mass of the radically polymerizable compound (D). The thiol compound (B) is preferably contained in an amount of 0.01 to 10 parts by mass relative to 100 parts by mass of the radical polymerizable compound (D). The mixture preferably contains 100 to 800 parts by mass of the inorganic aggregate (E) relative to 100 parts by mass of the radical polymerizable compound (D).

[0074] The silane coupling agent is preferably represented by the general formula YCH2SiX3 (wherein X is a hydrolyzable substituent and Y is an organic functional group). The X is preferably at least one of a methoxy group and an ethoxy group. The Y is preferably any one selected from the group consisting of a methacryloyloxy group, a vinyl group, an epoxy group, and an amino group.

[0075] [Restored inorganic structure] The inorganic structure according to the present invention has a repaired portion obtained by applying a mixture obtained by mixing the radical polymerizable resin composition containing the above (A) to (D) with the above inorganic aggregate (E) to a damaged portion of the inorganic structure and curing the mixture.

[0076] The repaired area was immersed in water at room temperature for 24 hours, and then the adhesive strength between the inorganic structure repair material and the damaged area was 1.0 N / mm 2 The adhesive strength can be 1.0N / mm or more. 2 By satisfying the above, good adhesion to the inorganic structure can be ensured. EXAMPLES

[0077] The present invention will be described below based on examples, but the present invention is not limited to these examples.

[0078] In the following Examples 1 to 6 and Comparative Examples 1 and 2, the following raw materials were used. <Metal-containing compounds (A)> Manganese octylate (manufactured by Toei Kako Co., Ltd., manganese hexoate, manganese content in total product: 6% by mass, molecular weight: 341.35) <Thiol Compound (B)> Bifunctional secondary thiol, KarenzMT (registered trademark) BD1 (1,4-bis(3-mercaptobutyryloxy)butane, molecular weight 299.43, manufactured by Showa Denko K.K.) <Radical polymerization initiator (C)> Cumene hydroperoxide (CHP), Percumyl (registered trademark) H-80, manufactured by NOF Corporation <Radical polymerizable compound (D)> Radical Polymerizable Compound (D-1) Urethane Acrylate Resin Lipoxy (registered trademark), Showa Denko K.K., KRN-880 Radical Polymerizable Compound (D-2) Vinyl Ester Resin Lipoxy (registered trademark), Showa Denko K.K., NSR-112 <Aggregate (E)> Premixed aggregate (E-1): A mixture of 15 parts by mass of high-early-strength Portland cement, 20 parts by mass of calcium carbonate TM-2, 55 parts by mass of N50 silica sand, and 10 parts by mass of N40 silica sand was used. Silane coupling agent (E-2): 3-methacryloxypropyltrimethoxysilane, Shin-Etsu Chemical Co., Ltd., KBM-503

[0079] <Compressive strength test> Test inorganic structure repair materials (Examples 1 to 6, Comparative Examples 1 and 2) were prepared with the formulations shown in Table 1 in accordance with JIS A 1132:2020. The dimensions of the test inorganic structure repairing materials (Examples 1 to 6, Comparative Examples 1 and 2) were 50 mm in diameter and 100 mm in height, and a steel mold was used. The tests were carried out using a Shimadzu concrete compression tester "CCM-1000kNI" (manufactured by Shimadzu Corporation). The tests were carried out after preparing the inorganic structure repair materials for testing (Examples 1 to 6, Comparative Examples 1 and 2) and curing them as required. The test results are shown in Table 1. The "normal curing" in Table 1 is the result of curing for one day at a temperature of 25°C and a humidity of 50%, after which a compressive strength test was conducted. The "immersion curing" in Table 1 shows the results of immersion in ion-exchanged water in an environment at 25°C, curing for one day, and then conducting a compressive strength test. As a restoration material for inorganic structures, it has a compressive strength of 5N / mm 2 The above was evaluated as "good." The evaluation results are shown in Table 1 below.

[0080] <Tensile strength test> Test inorganic structure repair materials (Examples 1 to 6, Comparative Examples 1 and 2) were prepared as 1A-type test pieces with the formulations shown in Table 1 in accordance with JIS K 7161-2:2014, 6.1 and 6.2. The tensile strength in Table 1 is a value measured in accordance with JIS K 7161-2:2014. The measurements were performed using an electromechanical universal material testing machine "5900R" (manufactured by Instron) at a test speed of 5 mm / min, and values ​​were obtained based on JIS K 7161-1: 2014. The test results are shown in Table 1. The "normal curing" in Table 1 is the result of curing for one day at a temperature of 25°C and a humidity of 50%, after which a tensile strength test was conducted. The "immersion curing" in Table 1 shows the results of immersion in ion-exchanged water in an environment at 25°C, curing for one day, and then conducting a tensile strength test. From the viewpoint of conformity to cracks, a breaking elongation rate of 1% or more and 15% or less was evaluated as "good." The evaluation results are shown in Table 1 below.

[0081] <Adhesion strength test under standard curing> An adhesion strength test under standard curing was carried out using a normal concrete plate (60×300×300) specified in JIS A 5371-2010 and test inorganic structure repair materials (Examples 1 to 6, Comparative Examples 1 and 2). The surface of the ordinary concrete slab to be used for the adhesion test was prepared by thoroughly removing any brittle or powdery material and wiping it with a soft, clean cloth. Preparation of the test inorganic structure repair materials (Examples 1 to 6, Comparative Examples 1 and 2) was performed in accordance with Section 7.4 of JIS A 6909:2014. The test inorganic structure repair materials (Examples 1 to 6, Comparative Examples 1 to 2) were coated with a radical polymerizable resin composition using a trowel or spatula to a thickness of approximately 10 mm, and then cured for one day at a temperature of 25°C and a humidity of 50%, after which an adhesion test was performed. The concrete formwork for the adhesion tests was set up according to Section 7.10 of JIS A 6909:2014. However, because the sizes of the test specimens differed, a rubber plate or the like 10 mm wide and 10 mm thick was used in place of the formwork, and the rubber plate was attached to an ordinary flat concrete plate with double-sided tape or the like to prepare test specimens for evaluating adhesion strength (Examples 1 to 6, Comparative Examples 1 and 2), and normal curing tests were performed. The bond strength test was performed using a Construction Research Institute-type adhesive strength tester (Technotester Model R-10000ND), a tensile tester certified by the Architectural Finish Society of Japan, by selecting five locations from each concrete plain slab specimen and conducting bond strength tests, and the average value of the five test locations was calculated. The test results are shown in Table 1. In addition, after the test was completed, the fracture morphology of the test specimen was visually observed, and it was rated as "cohesive failure" if the inside of the test specimen was the cause of the fracture, "substrate failure" if the concrete plate was the cause of the fracture, and "interface failure" if the interface between the concrete plate and the test specimen was destroyed. In the present invention, "substrate destruction" is preferred. The adhesive strength test was conducted with a bond strength of 1.0 N / mm from the viewpoint of adhesion to inorganic structures. 2 The above was evaluated as "good." The evaluation results are shown in Table 1 below.

[0082] <Adhesion strength test during immersion curing> The same test as the above <Adhesive strength test under standard curing> was carried out, except that the test conditions were changed as follows. The test results are shown in Table 1. The concrete formwork for the adhesion test was set up with reference to JIS A6909:2014, section 7.10. However, since the size of the test specimens was different, a rubber plate with a width of 10 mm and a thickness of 10 mm was used instead of the formwork, and the rubber plate was attached to a normal concrete plate with double-sided tape, etc., to prepare test specimens for evaluating adhesion strength (Examples 1 to 6, Comparative Examples 1 to 2). The test specimens were submerged in water for 24 hours so that they were sufficiently hydrated. After that, 5 mm from the top side was exposed to the water surface, and a wet test was performed with reference to the method described in Figure 8 of the test procedure after immersion in water in JIS A 6909:2014, section 7.10. In addition, the concrete surface was wiped with a dry cloth until no floating water remained on it just before applying the adhesive. Test inorganic structure repair materials (Examples 1 to 6, Comparative Examples 1 and 2) were prepared with the formulations shown in Table 1 in accordance with JIS A 1132:2020. The dimensions of the test inorganic structure repairing materials (Examples 1 to 6, Comparative Examples 1 and 2) were 50 mm in diameter and 100 mm in height, and a steel mold was used. The tests were carried out using a Shimadzu concrete compression tester "CCM-1000kNI" (manufactured by Shimadzu Corporation). The above tests were carried out after preparing the inorganic structure repair materials for testing (Examples 1 to 6, Comparative Examples 1 and 2) and curing them as required. The test results are shown in Table 1. The "normal curing" in Table 1 is the result of curing for one day at a temperature of 25°C and a humidity of 50%, after which a compressive strength test was conducted. The "immersion curing" in Table 1 shows the results of immersion in ion-exchanged water in an environment at 25°C, curing for one day, and then conducting a compressive strength test. As a restoration material for inorganic structures, it has a compressive strength of 5N / mm 2 The above was evaluated as "good." The evaluation results are shown in Table 1 below.

[0083] <Crack follow-up test> The test specimen in Figure 1 was prepared at 25°C and a crack tracking test was conducted. Specifically, the concrete was poured using the repair material as a partition plate and cured for 28 days. The repair material was then poured and cured for one day to obtain the test specimen. Both ends of the concrete were fixed with screws. The specimen was placed in a mold with an inner diameter of 100 x 100 x 400 mm as shown in Figure 2, and observed for 10 cycles, with one cycle consisting of "3 hours at -20°C", then "3 hours at 50°C", and finally "18 hours at 25°C". At -20°C, the concrete contracted and the repair material was stretched. At 50°C, the concrete expanded and the repair material was compressed. After each cycle, the repair material and the interface with the concrete were observed for cracks, and if there was no damage after 10 cycles, it was rated as "○", and if cracks appeared before the end of 10 cycles, it was rated as "×". The evaluation results are shown in Table 1 below.

[0084] [Table 1] [Industrial Applicability]

[0085] The inorganic structure repair material of the present invention can harden not only under dry conditions but also in the presence of a large amount of water or in a wet location, and is therefore useful as a coating, repair or paint for, for example, marine structures, concrete fume pipes for water supply and sewage systems and agricultural and water-related facilities, and concrete surfaces submerged in water, such as brackish water areas, seawater areas or river areas.

Claims

1. An inorganic structure repair material comprising a radical polymerizable resin composition containing the following (A) to (D) and the following (E) inorganic aggregate, and satisfying the following (physical property 1) and (physical property 2): The following (A) is contained in an amount of 0.001 to 5 parts by mass in terms of a metal component per 100 parts by mass of the following (D), The composition contains 0.01 to 10 parts by mass of the following (B) per 100 parts by mass of the following (D), The composition contains 0.1 to 10 parts by mass of the following (C) per 100 parts by mass of the following (D), The following (D) is at least one selected from the group consisting of vinyl ester resins (epoxy (meth)acrylate resins), unsaturated polyester resins, polyester (meth)acrylate resins, urethane (meth)acrylate resins, (meth)acrylate resins, and radical polymerizable unsaturated monomers, The radical polymerizable unsaturated monomer is a compound having a vinyl group or a (meth)acryloyl group, The content of the radical polymerizable unsaturated monomer is 90% by mass or less in the following (D), The inorganic structure repair material, wherein the content of the following (D) in the radical polymerizable resin composition is 10 to 99.9 mass %: (A) One or more metal-containing compounds selected from metal soaps (A1) and metal complexes having a β-diketone skeleton (A2). (B) One or more thiol compounds selected from secondary thiol compounds (B1) and tertiary thiol compounds (B2). (C) Radical Polymerization Initiator (D) Radical polymerizable compound (E) An inorganic aggregate treated with 0.001 to 15 parts by mass of a silane coupling agent relative to 100 parts by mass of a radical polymerizable compound (D). (Physical Property 1) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. The breaking elongation is 1 to 15%. (Physical Property 2) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. After that, the compressive strength is 5 to 40 N / mm 2

2. 2. The inorganic structure repairing material according to claim 1, comprising 100 to 800 parts by mass of the inorganic aggregate (E) per 100 parts by mass of the radical polymerizable compound (D).

3. The silane coupling agent is represented by the general formula YCH 2 Six 3 3. The inorganic structure repair material according to claim 1 or 2, which is represented by the formula: [wherein X is a hydrolyzable substituent and Y is an organic functional group].

4. The inorganic structure repairing material according to claim 3 , wherein the X is at least one of a methoxy group and an ethoxy group.

5. The inorganic structure repairing material according to claim 3, wherein Y is any one selected from the group consisting of a methacryloyloxy group, a vinyl group, an epoxy group, and an amino group.

6. A method for repairing an inorganic structure, comprising applying a mixture containing a radical polymerizable resin composition containing the following (A) to (D) and the following inorganic aggregate (E), the mixture satisfying the following physical properties, to a damaged part of the inorganic structure and curing the mixture: The following (A) is contained in an amount of 0.001 to 5 parts by mass in terms of a metal component per 100 parts by mass of the following (D), The composition contains 0.01 to 10 parts by mass of the following (B) per 100 parts by mass of the following (D), The composition contains 0.1 to 10 parts by mass of the following (C) per 100 parts by mass of the following (D), The following (D) is at least one selected from the group consisting of vinyl ester resins (epoxy (meth)acrylate resins), unsaturated polyester resins, polyester (meth)acrylate resins, urethane (meth)acrylate resins, (meth)acrylate resins, and radical polymerizable unsaturated monomers, The radical polymerizable unsaturated monomer is a compound having a vinyl group or a (meth)acryloyl group, The content of the radical polymerizable unsaturated monomer is 90% by mass or less in the following (D), The method for repairing an inorganic structure, wherein the content of the following (D) in the radical polymerizable resin composition is 10 to 99.9 mass %: (A) One or more metal-containing compounds selected from metal soaps (A1) and metal complexes having a β-diketone skeleton (A2). (B) One or more thiol compounds selected from secondary thiol compounds (B1) and tertiary thiol compounds (B2). (C) Radical Polymerization Initiator (D) Radical polymerizable compound (E) An inorganic aggregate treated with 0.001 to 15 parts by mass of a silane coupling agent relative to 100 parts by mass of a radical polymerizable compound (D). (Physical Property 1) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. The breaking elongation is 1 to 15%. (Physical Property 2) The radical polymerizable resin composition and the inorganic aggregate are mixed, and the mixture is immersed in water at room temperature for 24 hours. After that, the compressive strength is 5 to 40 N / mm 2

7. 7. The method for repairing an inorganic structure according to claim 6, wherein the mixture contains 100 to 800 parts by mass of the inorganic aggregate (E) per 100 parts by mass of the radical polymerizable compound (D).

8. The silane coupling agent is represented by the general formula YCH 2 Six 3 8. The method for repairing an inorganic structure according to claim 6 or 7, wherein the compound is represented by the formula: wherein X is a hydrolyzable substituent and Y is an organic functional group.

9. 9. The method for repairing an inorganic structure according to claim 8, wherein the X is at least one of a methoxy group and an ethoxy group.

10. 9. The method for repairing an inorganic structure according to claim 8, wherein the Y is any one selected from the group consisting of a methacryloyloxy group, a vinyl group, an epoxy group, and an amino group.

11. The method for repairing an inorganic structure according to any one of claims 6 to 10, wherein the mixture is left to stand for 30 minutes or more, and then applied to the damaged area and cured.

Citation Information

Patent Citations

  • Hydraulic pressure controller for automatic transmission

    JP1982043043A

  • Resin concrete and resin mortar

    JP1997086992A

  • Resin concrete and resin mortar

    JP1998045453A

  • Epoxy resin composition for artificial marble and method for producing the epoxy resin composition

    JP2007169539A

  • Concrete structure repairing method

    JP2013256835A